A Meta-Heuristic Solution Approach for the Destruction of Moving Targets through Air Operations - Ucar, Ukbe; Isleyen, Selcuk Kursat (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
Moving Target Traveling Salesman Problem is the problem of destruction of targets moving at certain angles and speeds by a constant velocity pursuer. The problem is applied in many areas, mainly production, defense and surveillance systems. Military operations constitute the most strategic branch of these areas of application. In this study, a new solution algorithm is proposed based on simulated annealing for destruction of moving targets through air operations at minimum time. Six different heuristic algorithms, three of which were used for the first time, were developed for the initial solution of the algorithm, and the best two constructors were used as the initial solution in simulated annealing algorithm. Effectiveness of the proposed algorithms were tested on 20 different scenarios and it was found that the SA-MDH method (minimum distance - simulated annealing algorithm) gives better results than the SA-MTH method (minimum time - simulated annealing algorithm).